2019
DOI: 10.1080/17453674.2019.1599253
|View full text |Cite
|
Sign up to set email alerts
|

Revision of trapeziometacarpal arthroplasty: risk factors, procedures and outcomes

Abstract: Background and purpose — Revision surgery after trapeziometacarpal arthroplasty is sometimes required. Varying revision rates and outcomes have been reported in rather small patient series. Data on risk factors for revision surgery, on the final outcome of revision, and possible factors affecting the outcome of revision are also limited. We evaluated these factors in 50 patients. Patients and methods — From 1,142 trapeziometacarpal arthroplasties performed during a 10-year period, 50 patients with 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
2
23
1
1
Order By: Relevance
“…This is in contrast to the findings of a small matched-pair study showing neither any differences in pain nor hand function between patients after trapeziectomy for failed implant arthroplasty or primary trapeziectomy (Kaszap et al, 2013). Nevertheless, our scores are in line with or slightly better than those reported by other groups reporting on pain (lying between 2.8 and 4.2 on the numeric rating scale) after revision surgery (Mattila and Waris, 2019;Megerle et al, 2011;Munns et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the findings of a small matched-pair study showing neither any differences in pain nor hand function between patients after trapeziectomy for failed implant arthroplasty or primary trapeziectomy (Kaszap et al, 2013). Nevertheless, our scores are in line with or slightly better than those reported by other groups reporting on pain (lying between 2.8 and 4.2 on the numeric rating scale) after revision surgery (Mattila and Waris, 2019;Megerle et al, 2011;Munns et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Trapezium resection alone or with ligament reconstruction and tendon interposition (LRTI) offers considerable pain relief and functional restoration in patients with thumb carpometacarpal (CMC) osteoarthritis (OA) (Vermeulen et al., 2011; Wajon et al., 2015; Yeoman et al., 2019). Despite the mainly good outcomes, 2.5% to 5% of patients require revision surgery due to persistent pain, instability, subsidence of the first metacarpal (MC) bone, weakness and/or untreated peritrapezial or other midcarpal OA (Cooney et al., 2006; Hess et al., 2018; Mattila and Waris, 2019; Munns et al., 2019). Younger patients tend to have a higher risk for revision surgery than older patients (Mattila and Waris, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, an evaluation of repeat surgery for the treatment of the first metacarpal instability and/or hardware failure is not included in our study design; the management of such complications has been previously reported. 22 Patients who receive an intra-articular corticosteroid injection within 3 months before surgery for CMC joint arthritis of the thumb may be at increased risk in the first 90 days postoperatively for additional surgery to treat a wound complication/infection. Although further studies are needed to draw definitive conclusions, intra-articular injections may be a modifiable risk factor for infection in the 3 months before surgery to treat thumb CMC joint arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…28 In comparison, the revision rate for trapeziectomy (including those with and without LRTI) is said to be 4.6% at 10 years. 29 It may be hard to justify the small functional and symptom improvement conferred by joint replacement when revision rates are much higher than that of trapeziectomy. Moreover, trapeziectomy with LRTI has been shown to confer a greater degree of thumb opposition than joint replacement, with equivalent VAS pain scores, pinch strength, and grip strength.…”
Section: Discussionmentioning
confidence: 99%